The Leader’s Guide to Mindfulness (getAbstract Summary). - , getAbstract (linkedin.com, 2019)
In this audio-only summary of psychologist Audrey Tang's book, learn how leaders at any level can benefit from mindfulness and explore practical ways to implement it daily.